SAR Reduction Using Integration of PIFA and AMC Structure for Pentaband Mobile Terminals - Jae-Gon Lee; Jeong-Hae Lee (International Journal of Antennas and Propagation)
In this paper, a capacitive grating artificial magnetic conductor (AMC) is presented to reduce the specific absorption rate (SAR) in pentaband mobile terminals. The AMC structure is implemented using a dielectric film with the printed arrays of the metal strips placed at the top and the bottom of the dielectric. It is difficult to design the AMC structure to operate at low (824~960 MHz) and high bands (1710~2170 MHz) simultaneously, because of the limited space available for the antenna. Hence, we have designed the capacitive grating AMC to operate at a high band. Then, we attached a PIFA to the AMC structure to cover low and high bands. As the AMC structure is operated as a perfect electric conductor (PEC) in low band, the radiating branches of the PIFA for the low and high bands should be located on the non-AMC and the AMC structures, respectively. Even though the AMC structure is operated at a high band, the effect against the head could be reduced in the pentaband due to the spreading effect of the electromagnetic (EM) field at lower bands. From measured results, the 1 g SAR in the case of the AMC antenna is significantly lower than that in the case where only the PIFA is present in the pentaband.